2015
DOI: 10.1016/j.actamat.2014.07.067
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modeling of defect formation during solid-phase epitaxy regrowth of silicon

Abstract: This work presents a multiscale approach to understanding the defect formation during the evolution of solid-phase epitaxy regrowth in Si. A molecular dynamics (MD) simulation technique has been used to elucidate the defect formation mechanisms, as well as to determine their nature. A hybrid lattice kinetic Monte Carlo (LKMC)-finite element method (FEM) model fed by the outcome of MD was subsequently implemented. It scales up the simulation times and sizes, while reproducing the important features of the defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
(20 reference statements)
0
13
1
1
Order By: Relevance
“…Some models explain the a-Si SPER process growth fronts exhibit nano-facets [9] and form defects at the {1 1 1} interface with intrinsic and extrinsic stress. The intrinsic stress comes from the intrinsic a-Si/Si density difference and the volumetric expansion strain effect [10]. And the extrinsic stress comes from the capping high-stress film.…”
Section: Introductionmentioning
confidence: 99%
“…Some models explain the a-Si SPER process growth fronts exhibit nano-facets [9] and form defects at the {1 1 1} interface with intrinsic and extrinsic stress. The intrinsic stress comes from the intrinsic a-Si/Si density difference and the volumetric expansion strain effect [10]. And the extrinsic stress comes from the capping high-stress film.…”
Section: Introductionmentioning
confidence: 99%
“…Stresses can be externally generated or appear as a result of the 2% volume expansion of amorphous Si with respect to crystal Si [108]. CMD simulations have shown that the anisotropic regrowth of the amorphous phase in thin film layers results in twin defects [102,109,110], and that when significant strains are present, a slow-down in zones with high shear strain produces the evolution of ledges that collapse and evolve into Frank partial loops [111].…”
Section: Atomistic Kmc Modelsmentioning
confidence: 99%
“…To overcome the limitations of non-lattice KMC models in a computationally efficient code, Martin-Bragado et al developed a lattice KMC model that reproduces different planar SPER velocities and the formation of defects during regrowth [94,[111][112][113]. Stress information can be extracted from finite-element methods [111] and fed back and forth to the lattice KMC code.…”
Section: Atomistic Kmc Modelsmentioning
confidence: 99%
See 2 more Smart Citations